EFFECT OF CORPORATE SOCIAL RESPONSIBILITY OF WELFARE SOCIETY - Muhammad Thamrin; Desi Novita; Rosa Aini (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this study was to (1) describe the empowerment of local communities PTPN IV Kebun Balap through PKBL,(2) knowing how public perception and management company of the Program PKBL in PTPN IV Kebun Balap, (3) knowing how the impact before and after administration of PKBL funds for public welfare seen from the difference in capital, sales turnover, labor and benefits at the time before and after crediting. The sample used in this study is composed of the management company and the community built Partnership namely to see and compare the state at the time before and after the PKBL. Data were analyzed using analysis of different test average of two groups of pairs. Paired samples ( paired sample ) is a sample / group with the same subject but have two different treatments or measurements. Results of the study were obtained difference in the average amount of capital , turnover , employment and profits at the time before and after the PKBL.Keywords : CSR, PKBL, Community Welfare